Implant quality assurance: detection of abscessed implants and their effect on feedlot performance of beef heifers - M.F. Spire; J.M. Sargeant; Dale A. Blasi; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1999)
Infrared thermography (IRT) can be used successfully to differentiate abscessed implanted ears from nonimplanted ears 8 days postimplanting. Abscessed ears averaged 5.7EF warmer than nonimplanted ears when ambient temperature was 60 to 63EF. Average daily gain and feed efficiency were reduced 8.9% and 8.3%, respectively, over the 91-day feeding period for cattle with abscessed implants compared to cattle with normal implants. Dry matter intake was not affected by an abscessed implant and averaged nearly 18.0 lb/head/day for both treatment groups. Abscessed implants reduced economic return by 17.70 per head.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Infrared thermography; Abscessed implants; Feedlot performance